2015
DOI: 10.3390/toxins7093512
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Characterization and Secondary Metabolite Profiling of Aspergillus Section Aspergillus Contaminating Feeds and Feedstuffs

Abstract: Xerophilic fungal species of the genus Aspergillus are economically highly relevant due to their ability to grow on low water activity substrates causing spoilage of stored goods and animal feeds. These fungi can synthesize a variety of secondary metabolites, many of which show animal toxicity, creating a health risk for food production animals and to humans as final consumers, respectively. Animal feeds used for rabbit, chinchilla and rainbow trout production in Argentina were analysed for the presence of xer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 71 publications
3
11
0
Order By: Relevance
“…Echinulin was first discovered in A. brunneus (= E. echinulatum) by Quilico and Panizzi (1943). It was subsequently detected in many more section Aspergillus species (Ali et al 1989;Almeida et al 2010;Greco et al 2015;Li et al 2008b;Slack et al 2009;Smetanina et al 2007;Vesonder et al 1988) and shown to be toxic to animal cells (Ali et al 1989;Umeda et al 1974), while swine and mice respectively refused feed and water containing echinulin (Vesonder et al 1988). The presence of echinulin in the environment is not well documented however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinulin was first discovered in A. brunneus (= E. echinulatum) by Quilico and Panizzi (1943). It was subsequently detected in many more section Aspergillus species (Ali et al 1989;Almeida et al 2010;Greco et al 2015;Li et al 2008b;Slack et al 2009;Smetanina et al 2007;Vesonder et al 1988) and shown to be toxic to animal cells (Ali et al 1989;Umeda et al 1974), while swine and mice respectively refused feed and water containing echinulin (Vesonder et al 1988). The presence of echinulin in the environment is not well documented however.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, compounds from A. chevalieri were shown to be active against Plasmodium falciparum (malaria), Mycobacterium tuberculosis and cancer cell lines (Kanokmedhakul et al 2011), an antitumor compound was reported from A. cristatus (Almeida et al 2010), while many compounds are known to be antioxidants. They also produce mycotoxins, especially echinulin, flavoglaucin and physcion, which are toxic to animals (Ali et al 1989;Bachmann et al 1979;Cole and Cox 1981;Greco et al 2015;Nazar et al 1984;Rabie et al 1964;Semeniuk et al 1971;Slack et al 2009;Vesonder et al 1988), but toxicity has not been reported in humans. These species are not considered significant human pathogens, because most infections are superficial, with few cases of invasive infections known (de Hoog et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus are generally referred to as osmo-, xero- or halotolerant. They have a world-wide distribution and are common in indoor air, house dust, cereals, food products containing high concentrations of sugar, such as syrups, jams and jellies, salted meat products, semi-dry foods, feeds, leather goods and so on ( Raper and Fennell, 1965 , Blaser, 1975 , Chelkowski et al., 1987 , Pitt and Hocking, 2009 , Samson et al., 2010 , Greco et al., 2015 ). Species in this section are able to initiate growth at minimum moisture levels, thus establishing bridgeheads and facilitating the invasion of slightly less xerophilic molds ( Semeniuk et al., 1947 , Raper and Fennell, 1965 , Kozakiewicz, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus cristatus or “Golden Flower Fungus” is used in the production of Fuzhuan brick tea in China ( Wen, 1990 , Qi and Sun, 1990 , Xu et al., 2011 ); Aspergillus pseudoglaucus (= Eurotium repens ) is used as a starter culture in the manufacturing of katsuobushi and fish sauce ( Hayakawa et al., 1993 , Dimici and Wada, 1994 ); A. pseudoglaucus , A. chevalieri and A. montevidensis are frequently isolated from meju (dried fermented soybeans); two newly described species A. cibarius and A. cumulatus are also isolated from meju or meju fermentation related environment ( Hong et al., 2011 , Hong et al., 2012 , Kim et al., 2014 ). Aspergillus chevalieri , A. cristatus , A. glaucus , A. montevidensis , A. proliferans , A. pseudoglaucus and A. ruber have been reported from feedstuffs very often ( Pitt and Hocking, 2009 , Samson et al., 2010 , Greco et al., 2015 ). These species have also been reported from other habitats and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) in their studies on molecular screening of xerophilic Aspergillus strains; (iii) Schulthess & al. (2014) for their identifications of clinical moulds; and (iv) Greco & al. (2015) in their characterization of species on feeds and feedstuff.…”
Section: Edited By Jefferson Prado James Lendemer and Erin Trippmentioning
confidence: 99%